The MapReduce based approach to improve the all-pair shortest path computation - Lau Nguyen Dinh (Utan Kayu Publishins, 2024)
When building sequential algorithms for problems on the graphic network, the algorithms themselves are not only very complex but the complexity of the algorithms also is very big. Thus, sequential algorithms must be parralled to share work and reduce computation time. For above reasons, it is crucial to build parallelization of algorithms in extended graph to find the shortest path. Therefore, a study of algorithm finding the shortest path from a source node to all nodes in the MapReduce architectures is essential to deal with many real problems with huge input data in our daily life. MapReduce architectures processes on (Key, Value) pairs are independent between processes, so multiple processes can be assigned to execute simultaneously on the Hodoop system to reduce calculation time